2006
DOI: 10.1016/j.febslet.2006.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Insight in eukaryotic ABC transporter function by mutation analysis

Abstract: With regard to structure-function relations of ATPbinding cassette (ABC) transporters several intriguing questions are in the spotlight of active research: Why do functional ABC transporters possess two ATP binding and hydrolysis domains together with two ABC signatures and to what extent are the individual nucleotide-binding domains independent or interacting? Where is the substrate-binding site and how is ATP hydrolysis functionally coupled to the transport process itself? Although much progress has been mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 278 publications
3
59
0
1
Order By: Relevance
“…The 1034 and 1042 mutations lie in the middle of predicted TM helix 11, which has been hypothesized to be part of a drug binding site in HuMDR1 [12][13][14]. TM11 has also been implicated in the release of drug during ATP hydrolysis [15]. Thus our finding that the S1034C substitution has the most significant effect on PfMDR1 ATPase drug stimulation is consistent with previous drug interaction domain analyses for other ABC proteins.…”
supporting
confidence: 89%
“…The 1034 and 1042 mutations lie in the middle of predicted TM helix 11, which has been hypothesized to be part of a drug binding site in HuMDR1 [12][13][14]. TM11 has also been implicated in the release of drug during ATP hydrolysis [15]. Thus our finding that the S1034C substitution has the most significant effect on PfMDR1 ATPase drug stimulation is consistent with previous drug interaction domain analyses for other ABC proteins.…”
supporting
confidence: 89%
“…To our surprise, we did not observe any abnormal phenotypes (data not shown). It has been reported that a glycine to asparagine mutation in either of two ABC signatures of ABC proteins can abolish their ATP hydrolysis and transport functions without effects on the substrates binding activity (Ren et al, 2004;Frelet and Klein, 2006). Thus, we constructed an ABCC5 mutant vector pRc/CMV2-ABCC5-G1322D, in which the glycine at 1322 of wild-type zebrafish ABCC5 was mutated to an asparagine.…”
Section: Zebrafish Abcc5 Functions In Embryonic Developmentmentioning
confidence: 99%
“…In eukaryotes, the ABC transporters are located in the plasma membrane and the membranes of intracellular compartments such as the Golgi, endosomes and in the mitochondria [61]. When comparing various ABC transporter subfamilies -one major difference between the transporters is the presence of the additional N-terminal extension in a transmembrane domain (called TMD0) in some members of the ABCC-subfamily [64]. In contrast, the order of the TMDs and nucleotide binding domains (NBDs) in the two-dimensional structure of most of the transporters is identical.…”
Section: Abc Transportersmentioning
confidence: 99%
“…In contrast, the order of the TMDs and nucleotide binding domains (NBDs) in the two-dimensional structure of most of the transporters is identical. Membrane-associated ABC transporters have been found in two forms, the full-length transporters that are characterized by two identical halves each containing the NBD and the half-transporters that function as homo-or heterodimers ( Figure 1) [53][54][55]64]. As one of the best studied ABC transporters, the multidrug resistance (MDR1) P-glycoprotein (P-gp), also known as ABCB1, is a glycosylated membrane-associated enzyme 860 npg of the full-length form comprising 1 280 amino acids (with a molecular weight of 170 kDa), and is characterized by two identical halves, each with one NBD; it exports a wide range of diverse substrates [54,55,57].…”
Section: Abc Transportersmentioning
confidence: 99%
See 1 more Smart Citation